2021
DOI: 10.1111/vsu.13606
|View full text |Cite
|
Sign up to set email alerts
|

Custom‐built constrained uniaxial and rotating hinge total knee replacement in cats: Clinical application, design principles, surgical technique, and clinical outcome

Abstract: Objective: To describe the design principles and evolution, surgical technique, and outcome for custom constrained (uniaxial and rotating hinge) total knee replacement (TKR) in cats.Study design: Retrospective case series. Animals: Nine cats with traumatic stifle luxation (n = 8) or severe distal femoral deformity (n = 1) were considered suitable candidates. Methods: Cats that met eligibility criteria and received a custom TKR between 2009 and 2018 by a single surgeon were included in this case series. Three g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 46 publications
(83 reference statements)
0
8
0
Order By: Relevance
“…The implant in this case was a custom-made constrained uniaxial and rotating hinge TKR. However, additional cases and research are required to evaluate the feasibility of TKR in cats [54].…”
Section: Total Knee Replacementmentioning
confidence: 99%
See 1 more Smart Citation
“…The implant in this case was a custom-made constrained uniaxial and rotating hinge TKR. However, additional cases and research are required to evaluate the feasibility of TKR in cats [54].…”
Section: Total Knee Replacementmentioning
confidence: 99%
“…The accuracy of corrective osteotomy surgery appears to be effectively increased by utilizing 3D-printing replica for accurate planning of the procedure [8,37]. This may also contribute to successful surgical outcomes [35,54]. Overall, based on the surgeons' professional knowledge, RP was deemed useful to the receiver by reducing the surgical time, morbidity, and mortality, as well as lowering overall costs [16].…”
Section: Corrective Osteotomiesmentioning
confidence: 99%
“…24 Careful preparation and attention to detail is crucial to avoid complications and errors that may lead to ligament damage or instability, loosening of the implant and pain. 4,14,15 In our experience, the tibial and femoral ostectomies are the most F I G U R E 9 Femoral component alignment in canine total knee replacement (TKR) performed with generic or patient-specific guides (PSGs). (A) In the frontal plane, varusvalgus alignment of the femoral component was similar in the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that surgical navigation improves tibial component alignment in canine TKR, 23 but without a commercial veterinary navigation system on the market, these benefits cannot be realized at present. However, most veterinary referral centers have easy access to CT scanning, and the clinical success of PSGs in other areas of veterinary orthopedics, including spine surgery and long bone deformity correction, [6][7][8][9][10][11][12][13][14] provides a strong rationale for exploring their utility in canine TKR. In this study, all the knees operated with the assistance of PSGs fell within 3 degrees of neutral in the frontal plane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation